Une copie de L’Origine du monde par René Magritte ? - Catherine Defeyt; David Strivay (CeROArt : Conservation, Exposition, Restauration d'Objets d'Art)
For more than 20 years, the copy of The origin of the world of Courbet, which Joseph-Marie Lo Duca attributed to René Magritte, has duped historians and amateurs. Although the deception was unmasked, the date of realization, the context of realization and the author of this copy remained unknown. The study of the work through imaging methods and scientific analysis seemed a way to provide some answers to these questions. The results obtained in the context of this study led to the conclusion that the present copy could not be earlier than 1945. Moreover, various material indices indicate that it was probably produced not according to the Courbet painting, but from a black and white reproduction.